A cozinha paraense no boom gomífero: uma análise sobre os Hábitos alimentares em Belém (1870-1900) - SILVA, Layse Fernanda Azevedo (2022)
This work analyzes the eating habits in Belém in the second half of the 19th century, from the perspective of food as a culture. In which, specifically, the objective is to identify the mestizo cuisine in the emergence of restaurants; describe how regional food was consumed and point out the different foods, subjects and establishments in the city of Belém. The sources are from newspapers dating from the end of the 19th century, between 1870-1900, which confirm the heyday of the rubber economy. Therefore, if Belém was in constant transformation in the second half of the 20th century, XIX due to the transformations that the rubber economy caused in the urban scene of Belém, the eating habits of this society followed this process of changes? If food is culture, how do the eating habits of this society reflect the changes that have taken place in the city of Belém? Restaurants emerged in this period following the model of refinement and modernity, in which the mestizo cuisine is identified in their menus, with regional, local and international dishes, and regional food, such as tucupi. The consumption of regional fish, turtle, tacacá, porridge, maniçoba and the consumption of açaí will also be analyzed, which allows me to visualize the different subjects in the world of food.